Analisis Konten Buku Ajar Bahasa Arab Kelas Enam Kementerian Agama - Ramadhani, Risma; Ridlo, Ubaid; Rahmawati, Siti Uriana; Arifin, Syamsul (Kopertais Wilayah I DKI Jakarta dan Banten, 2025)
This study aims to analyze the content of the Arabic language book for 6th-grade Madrasah Ibtidaiyah (MI) students, published by the Ministry of Religious Affairs of the Republic of Indonesia, written by Uswatul Hasanah, using content analysis based on Rusdi Ahmad Thuaimah's theory. The main focus of this research includes three aspects: vocabulary (mufradat), cultural elements, and exercises. This research employs a qualitative method with a literature study approach. Data was obtained from the 2020 edition of the Arabic language textbook for 6th-grade MI students published by the Ministry of Religious Affairs as the primary source, along with related literature as secondary sources. Data collection was conducted through documentation studies, while data analysis utilized content analysis methods based on Rusdi Ahmad Thuaimah's approach, covering language, culture, and exercise aspects. The results show that the book presents vocabulary in a structured and consistent manner, with 12 new words per lesson. However, the vocabulary provided does not meet the ideal standard recommended for the elementary level. In terms of culture, the book successfully incorporates Islamic and local cultural values but requires strengthening in presenting a broader diversity of Arab cultures. On the other hand, the exercises and evaluations provided do not fully support the development of language skills comprehensively. The findings indicate that while the book has strengths in terms of organization and visualization, further development is needed in the areas of material variety, depth of meaning, and contextualization to make Arabic language learning more communicative and comprehensive.